FAKTOR-FAKTOR YANG MENENTUKAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PEREMPUAN - Jaya, Herawati; Rosnani, Rosnani; Athiutama, Ari; Dwi, Wahyu; Kumalasari, Intan; Afdal, Afdal; Hayati, Wirda; Rahayu, Mesra (Media Penelitian dan Pengembangan Kesehatan, 2025)
In 2022, 2.3 million women were diagnosed with breast cancer worldwide. In 2022, 670,000 women died of breast cancer worldwide. This study aimed to analyze the factors that determine breast self-examination behavior (sadar) in adolescent girls. This study was conducted in the city of Palembang from April to June 2024. The design of this study was cross-sectional. The research team consisted of 18 teams spread to the smallest areas. Data collection used questionnaires and direct observation, with some ratio data categorized to facilitate statistical testing. The population of this study were adolescent girls aged 15-24 years who had both parents, lived with their parents, and were enrolled in high school at the time of data collection (inclusion criteria). The Chi-Square test was used for analysis, with data processing using computerized statistics at a 95% confidence level (α = 0.05). The results of this study indicate that behavior related to breast self-examination (BSE) is influenced by age (p = 0.010), ethnicity p = 0.000), social environment (p = 0.002), internet access (p = 0.011), information media (p = 0.000), family (p = 0.000), and peer influence (p = 0.000). In conclusion, there is a relationship between breast self-examination behavior and age, ethnicity, social environment conditions, internet access, information media, family influence, and peer influence. The implications of the findings of this study are the need to increase information and education regarding the importance of BSE in the early detection of breast cancer, especially for groups that are vulnerable to the disease.